OPTIMALISASI MEDIA SOSIAL PESANTREN UNTUK MEMBENDUNG KONTEN NEGATIF DI DUNIA MAYA - Farid, Achmad (Dakwah, 2019)
The emergence of new media era allows the spread of positive contents (inspiring and useful subject) and negative contents (hate speech and hoaxes) through cyberspace. Islamic Boarding Schools (Pondok Pesantren) which have large mass of santri (students) have a strategic position to repress the dissemination of mentioned negative content. The applied method is optimizing social media as a channel for spreading positive content with the spirit of rahmatanlil ?alamin. Key Words: New Media, Islamic Boarding School (Pondok Pesantren), the Spirit of Rahmatanlil ?Alamin